Primary School Teachers’ Readiness to Address the Transformation of Science Education through Artificial Intelligence: A Systematic Literature Review - Tia Nabela; Rohmani Rohmani (Institute of Multidisciplinary Research and Community Service, 2026)
Science education in elementary schools is still dominated by conventional methods, which are thus unable to optimally foster student engagement and conceptual understanding. Advances in Artificial Intelligence (AI) offer opportunities to transform learning into a more interactive and adaptive experience; however, its success depends heavily on teacher readiness. This study aims to describe and analyze elementary school teachers’ readiness in facing the transformation of science learning based on Artificial Intelligence (AI), including aspects of attitudes, competencies, and the ability to integrate AI technology into the learning process. The method used was a Systematic Literature Review (SLR) through the PRISMA approach, with the search process utilizing a combination of keywords (“Science Education” OR “Science Learning”), (“Artificial Intelligence” OR “AI”), (“Teacher Readiness” OR “Teacher Competence”), and (“Elementary School” OR “Primary School”) in the Scopus database from 2021–2025, resulting in 10 relevant and high-quality articles after the selection process. The results showed that teachers generally have positive attitudes, high interest, and strong acceptance of AI use in science learning, as it is considered capable of fostering more interactive, innovative, and student-centered learning processes in the digital era. However, teachers’ readiness in terms of technical and pedagogical competencies remains at a moderate and uneven level, particularly in operating AI technology and integrating it effectively into learning activities. In addition, limited digital literacy, lack of training, and inadequate infrastructure were identified as the main challenges, indicating the need to strengthen teachers’ competencies and provide adequate facilities to optimize AI implementation in science learning. This study highlights the importance of improving teachers’ digital competencies and providing technological support to ensure that AI is applied more effectively and optimally in science learning. Keywords: teachers’ readiness, artificial intelligence, elementary school, systematic literature review.